2020
DOI: 10.1002/jcp.30097
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone alleviates liver fibrosis via miR‐30a‐mediated epithelial‐mesenchymal transition

Abstract: Thymoquinone (TQ), the main active constituent of Nigella sativa seeds, has been shown to play a role in antioxidation, anti‐inflammation, and antitumor. Recent studies have demonstrated that TQ contributes to the suppression of liver fibrosis. Abnormal activated epithelial‐mesenchymal transition (EMT) promotes the activation of hepatic stellate cells (HSCs). However, whether the antifibrotic effects of TQ occur through inhibiting EMT is largely unknown. In this study, it was found that TQ ameliorated liver fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…HSC activation can be stimulated by a variety of factors, such as the pro-fibrogenic TGF-β1. Thus, a combination therapy approach that targets TGF-β, its regulating pathways and the associated inflammatory state may represent an option for liver fibrosis treatment ( Ebrahimkhani et al, 2011 ; Bai et al, 2013 ; Feng et al, 2013 ; Geng et al, 2020 ). In addition, other cytokines can stimulate the fibrotic process in the liver ( Tsuda et al, 2013 ; Youssef et al, 2013 ).…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…HSC activation can be stimulated by a variety of factors, such as the pro-fibrogenic TGF-β1. Thus, a combination therapy approach that targets TGF-β, its regulating pathways and the associated inflammatory state may represent an option for liver fibrosis treatment ( Ebrahimkhani et al, 2011 ; Bai et al, 2013 ; Feng et al, 2013 ; Geng et al, 2020 ). In addition, other cytokines can stimulate the fibrotic process in the liver ( Tsuda et al, 2013 ; Youssef et al, 2013 ).…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…Although the role of miR30a in tumors has been well established, its role in AIH warrants further study. Geng et al found that the herbal extract thymoquinone exerted an anti-brotic effect by upregulating miR30a expression, indicating the anti-brotic potential of miR30a in the liver 23 . Here, we aimed to explore the anti-liver in ammation potential of miR30a transfection in AIH, which is considered to be a liver disease relevant to autoimmunity and in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that activated HSCs play a pivotal role in the development of liver fibrosis, being responsible for the excessive accumulation of ECM proteins in the liver [ 127 ]. Another study found that it contributes to the amelioration of liver fibrosis by interfering with epithelial-mesenchymal transition (EMT) by regulating snail family translational repressor 1 (SNAI1), a zinc finger transcription factor protein involved in EMT [ 125 , 128 ].…”
Section: The Role Of Liver-derived Mirnas In Metabolic Regulation And...mentioning
confidence: 99%